Cognitive functioning in a group of adolescents at risk for psychosis - Mohn-Haugen, Caroline Ranem; Mohn, Christine; Larøi, Frank; Teigset, Charlotte M.; Øie, Merete Glenne; Rund, Bjørn Rishovd (Frontiers in Psychiatry, 2022)
Cognitive deficits are a core feature of schizophrenia, and impairments are present in groups at-risk for psychosis. Most at-risk studies include young adults and not younger age-groups, such as adolescents. Participants are usually help-seeking individuals, even though risk factors may also be present in non-help seeking adolescents. We aim to explore cognitive functions in a group of non-help-seeking 15-year-old adolescents at risk for psychosis compared to age- and gender matched controls, including particular focus on specific cognitive domains. Hundred participants (mean age = 15.3) were invited after completing the 14-year-old survey distributed by the Norwegian Mother-, Father- and Child Study. At-risk adolescents were selected based on high scores on 19 items assessing both psychotic experiences and anomalous self-experiences. Matched controls were selected from the same sample. Cognitive functioning was assessed using the MATRICS Consensus Cognitive Battery and IQ using Wechsler’s Abbreviated Test of Intelligence. We found that the adolescents at-risk for psychosis had significantly poorer scores than controls on the composite score of the MCCB. IQ scores were also significantly lower in the at-risk group. The results highlight general cognitive deficits as central in a group of non-help-seeking adolescents at-risk for psychosis. Results indicate that the development of cognitive impairments starts early in life in at-risk groups. It is still unclear whether specific cognitive domains, such as verbal learning, are related to psychotic symptoms or may be specifically vulnerable to symptoms of depression and anxiety.